Peningkatan Keterampilan Menulis Teks Cerita Moral (Fabel) dan Prestasi Belajar Bahasa Indonesia dengan Metode Inkuiri Peserta Didik Kelas VIII F SMPN 2 Bandar Mataram - Suhariyanto, Suhariyanto (STKIP PGRI Bandar Lampung, 2022)
The study aims to dscribe the write moral value tex by method of inquiry students VIII F SMPN 2 Bandar Mataram. Based on the analysis that has been reduction, display, and verification of data. Data colletion tes and non tes. Results and discussion write narrative of tex students VIII F SMPN 2 Bandar Mataram: 1) theme tex, 2) the story tex, 3) figures, 4) background drawing, 5) message story 6) sturctuce tex, 7) punctuation,8) background society.9) background wites, 10) value moral tex. Prosessing ability write eksposition tex since prasiclus, siclus I, siclus II, and siclus III to significant. Learning achievement prasiclus 5,93%, siclus I 7,51%, siclus II 8,48%, and siclus III 8,86%. The completness prasiclus 2 (6,89%), siclus I8 (62,06%, siclus II 26 (89,65%, siclus III 100%.